Model Inovasi Wirausaha Kain Tenun Baduy di Desa Kanekes, Leuwidamar, Lebak, Banten: Suatu Kajian - Wisber Wiryanto (Universitas Batanghari, 2022)
The village innovation program was launched to develop the popular economy including entrepreneurship through superior village products initiated by village devices. Meanwhile, the government has innovated through appropriate technology (TTG); village innovation program (PID); and the college conducts community service. However, village government officials and their communities are still not optimally utilizing the TTG and PID produced to develop villages towards entrepreneurial villages. Therefore, a research was conducted with problem formulation, how is the innovation model of Baduy woven fabric? The purpose research is to find out the innovation model of Baduy woven fabric. The research location in Kanekes Village, Leuwidamar, Lebak, Banten as a tourist village was studied in the third quarter of 2021. The method of research uses both field observation for primary data collection, as well as library studies by reading references and documents for relevant secondary data collection. The results showed that there was an innovation in Baduy woven fabrics both production and marketing through triple helix partnerships among stakeholders, namely the government, universities, and the business world to the artisan community, especially Baduy woven fabrics to improve the economy of Kanekes village.